R-MC46 monoclonal antibody stimulates adhesion and phagocytosis by rat macrophages - Gašić Sonja; Vučević Dragana; Popović Petar; Vasilijić Saša; Čolić Miodrag J. (Vojnosanitetski Pregled)
Background. In our previous experiments it was shown that R-MC46 monoclonal antibody (mAb), produced at our Institute, stimulated homotypic aggregation of rat granulocytes and production of proinflammatory cytokines. The aim of this study was to examine antigen expression and function, recognized by R-MC46 mAb on macrophages. Methods. The expression of R-MC46 antigen on thymic and peritoneal macrophages was investigated using immunocytochemistry and flow cytometry methods. Its biochemical characterization was performed by Western blot. The ability of R-MC46 mAb to modulate adhesion and phagocytosis by macrophages was studied by using co-culture experiments with autologous thymocytes. Results. R-MC46 mAb stained thymic macrophages more strongly than peritoneal macrophages. After in vivo treatment of peritoneal macrophages with Pristane, a significant up-regulation of the R-MC46 antigen expression was observed. Western blot analysis showed that the mAb recognized a low molecular weight antigen of about 5.5 kDa. R-MC46 mAb significantly enhanced binding and phagocytosis of thymocytes by both thymic and peritoneal macrophages. These processes were completely blocked by WT.3 (anti-CD18) mAb. The stimulation of binding thymocyte to macrophages was higher with the use of thymic macrophages,while the phagocytosis of these cells was higher in the presence of peritoneal macrophages. Conclusion. R-MC46 mAb recognized a new molecule expressed by rat macrophages. The antigen is most probably involved in β2 integrin-mediated adhesion and phagocytosis, as well as proinflammatory functions of macrophages.